A dynamic invertible intramolecular charge-transfer fluorescence probe: real-time monitoring of mitochondrial ATPase activity12. Issue 40 (3rd May 2017) - Zhang, Hua; Wang, Yafu; Xuan, Xiaopeng; Wang, Ge; Guo, Haiming; Fan, Jiangli
Abstract : A dynamic invertible intramolecular charge-transfer fluorescence probe was successfully utilized for the real-time monitoring of mitochondrial ATPase activity. Abstract : A dynamic invertible intramolecular charge-transfer (ICT) process could provide abundant response signals for real-time monitoring in living organisms. Herein, based on dynamic invertible ICT, we have reported a cancer cell-targeted fluorescence probe (OPM ) for mitochondrial ATPase activity. Due to its abundant response signals, OPM could real-time monitor mitochondrial ATPase activity during the cancer apoptosis process, successfully.